Integration of Energy Harvesting and Electrochemical Storage Devices. Issue 12 (12th October 2017) - Zhong, Yu; Xia, Xinhui; Mai, Wenjie; Tu, Jiangping; Fan, Hong Jin
Abstract: Multifunctional energy devices with various energy forms in different operation modes are under current research focus toward the new‐generation smart and self‐powered electronics. In this review, the recent progress made in developing integrated/joint multifunctional energy devices, with a focus on electrochromic batteries/supercapacitors, and solar cells powered batteries/supercapacitors, is summarized. The different integration modes and design strategies are highlighted and their merit/demerits are also discussed. The authors' opinions on future research toward smart multifunctional energy devices are provided at the end. Abstract : Marriage for better life . This review summarizes the latest advances in the integrated/joint smart multifunctional energy devices, with a focus on electrochromic batteries/supercapacitors and solar cells plus batteries/supercapacitors. The design concepts and their merit/demerits are discussed.